Evaluación de índices de cosecha (grano tierno y grano seco) del chocho (Lupinus mutabilis), en el sector Salache bajo, Latacunga, Cotopaxi, 2017 - Toaquiza Lema, Jessica Alexandra (2018)
The research topic "Evaluation of crops indexes (sweet grain and dry grain) of the lupine (Lupinus mutabilis), Low Salache Sector, Latacunga, Cotopaxi, 2017" had as specific objectives to determine the chronology of the corps indexes of the cultivation of lupine at different stages of maturity and establishing physical-chemical parameters of the grain at crops in the different stages of maturity of the seed. We worked with an experimental design of DBCA where 8 treatments were applied with 3 repetitions, the factors evaluated were the phenological stage (maturity of the grain) and the inflorescence disposition. Within the results it is deduced that the green grain 2 (158 days of crops) in the variable weight obtained 26.97 grams, for green grain 3 (164 days of crops) with 24.1 grams. The dry grain (172 days of harvest) obtained a weight of 16.32 grams and the green grain 1 (151 days of harvest) with a weight of 14.48 grams. The pH is in a range between 5.73 and 5.78 for the stages of maturity in green, it was not possible to measure the pH of the dry grain due to the hardness of the grain, in addition the solid-soluble content was measured only in green grain with a 4 ° Brix for the three green maturity indices. The firmness registered for the green and dry grain was 3.5 kg / cm2. In the moisture parameter, a high value of 32.86% was recorded for green bean 1 (151 harvest days), for green bean 2 (158 harvest days) the moisture content was 31.28%, for green bean 3 (165 days of harvest) the moisture content was 30.24% and the dry grain presented humidity of 10.21%. (172 harvest days). Regarding the incidence of pests diseases and physiopathies for green grain was zero, dry grain presented a percentage of 1.21% for this indicator. Differences were established within the physical-chemical parameters for the different stages of maturity due to the chronology of the harvest indexes